Suicidal behavior among indigenous Sami in Arctic Norway : a special focus on adolescents and young adults - Silviken, Anne C. (Universitetet i Tromsø, 2007)
Since the 1950’s the global suicide rates have continued to increase, and today suicide has become an important public-health problem worldwide (World Health Organization (WHO), 2002). According to WHO there are approximately one million deaths from suicide each year worldwide, and about 20 times this number of people attempt suicide (2002). There are substantial variations in the national suicide rates (Lester, 1997), and in addition great variation in rates within the same country and between different ethnic groups (Roberts, Chen & Roberts, 1997). During the last decades suicide rates have increased alarmingly among indigenous people, and especially among indigenous residing in the Arctic, such as the lnuit in Greenland (Leineweber et al., 2001) and in Canada (Sigurdson et al., 1994), and among Alaskan Natives in the US (Borowsky et al., 1999). The increase in suicide rates among indigenous people in the Arctic have been so alarmingly high that it has been described as an epidemic level (Bjerregaard & Lynge, 2006; Leenaars, 2006) and it has been declared that certain indigenous people have the highest suicide risk of any identifiable cultural (or ethnic) group (Leenaars, 2006; Kirmayer, 1994). Unfortunately, suicide has become the leading cause of death for young indigenous people, especially among males, and is a significant contributor to potential years of life lost. Although there is carried out research on the prevalence of suicidal behavior among several indigenous people, e.g. in Canada, Alaska, Greenland, Sweden, Australia, New Zealand, our understanding of suicidal behavior among indigenous people is still limited (Cutcliffe, 2005; Leenaars, 2006; Stewart, 2005). There is no registration of ethnicity in the national population register in Norway, for that reason there are neither official statistics of health and living conditions nor suicide rates for indigenous Sami (hereafter called Sami). There have so far been conducted limited research on health and living conditions among Sami in ...